THE ONTOLOGICAL DIMENSION OF LANGUAGE IN H. G. GADAMER'S HERMENEUTICS. - Laurukhin, Andrei (Problems / Problemos, 2016)
The subject of the analysis is the problem of interrelation of language, understanding, and being in H.-G. Gadamer's hermeneutics. The analysis is focused on Gadamer's equivocal and ambiguous thesis that "being that can be understood is language". The author reveals the fundamentally ontological background of Gadamer's hermeneutical analysis of language, and critically rethinks the interpretation of this thesis by a prominent researcher Jean Grondin.